Has the exchange rate pass through recently declined in the euro area? - Selin Özyurt (European Central Bank (ECB), 2016)
This study investigates the degree and speed of the exchange rate pass through (ERPT) into extra-euro area import prices for the euro area aggregate and the five largest countries. Based on quarterly frequency data, the analysis covers the period 1996Q1-2015Q2. Two alternative measures of the nominal exchange rate are used: the NEER of the euro against 38 partners and the EUR/USD bilateral exchange rate. The results show that the pass through is only “partial” in the euro area, most probably reflecting slow nominal price adjustments and the pricing-to-market behaviour of firms. We find clear evidence that the degree of pass through has been declining over the past two decades. Interestingly, the period of strong fall of pass through coincides with the increasing share of the emerging countries in world trade and the accession of China to the WTO. Looking at the largest euro area countries, we find striking heterogeneities in the degree but also in the speed of the ERPT. The lowest degree of pass through of a change in NEER is found for Germany while it is the highest for Italy. In addition, unlike the other large euro area countries, we do not find evidence for Italy of a decline in the degree of pass through over time. In a monetary union, such differences may signal large heterogeneities in domestic markets structures.
Keywords: E31; F3; F41; 330; euro area; Exchange rate pass-through; Import prices; pricing to market